Morbidity and mortality following poliomyelitis – a lifelong follow‐up. (21st November 2016) - Kay, L.; Nielsen, N. M.; Wanscher, B.; Ibsen, R.; Kjellberg, J.; Jennum, P.
Abstract : Background and purpose: In the world today 10–20 million people are still living with late effects of poliomyelitis (PM), but the long‐term consequences of the disease are not well known. The aim of this study was to describe lifelong morbidity and mortality among Danes who survived PM. Methods: Data from official registers for a cohort of 3606 Danes hospitalized for PM in the period 1940–1954 were compared with 13 762 age‐ and gender‐matched controls. Results: Compared with controls, mortality was moderately increased for both paralytic as well as non‐paralytic PM cases; Hazard Ratio, 1.31 (95% confidence interval, 1.18–1.44) and 1.09 (95% confidence interval, 1.00–1.19), respectively. Hospitalization rates were approximately 1.5 times higher among both paralytic and non‐paralytic PM cases as compared with controls. Discharge diagnoses showed a broad spectrum of diseases. There were no major differences in morbidities between paralytic and non‐paralytic PM cases. Conclusions: Poliomyelitis has significant long‐term consequences on morbidity and mortality of both paralytic and non‐paralytic cases.